Association of FOXO3 polymorphism (rs3800231) and clinical subphenotypes of beta thalassemic individuals - Torres, Flaviene F. [UNESP]; Bernardo, Victoria S. [UNESP]; Silva, Danilo G.H. [UNESP]; Okumura, Jéssika V.; Bonini-Domingos, Claudia R. [UNESP] (Elsevier, 2020)
Introduction: Studies have shown that the loss of the FOXO3 transcriptional function is involved in the pathophysiology of some chronic erythroid disorders, including beta-thalassemia (β-thal). Therefore, the single nucleotide polymorphism (SNP) rs3800231 (35-2764A > G) could contribute to alterations in its transcriptional activity, acting as a modifier of β-thal phenotypic manifestations. Objective and method: In order to better understand the genotypic and/or allelic distributions among β-thal patients, we evaluated 83 β-thal heterozygous and 20 homozygous, compared to 117 individuals without hemoglobinopathies (control group). Additionally, we verified any influence of the FOXO3 polymorphism on clinical manifestations among β-thal homozygotes. Results: We obtained higher frequencies of the wild-type homozygous (AA) and the wild-type allele (A) in the β-thal group (p < 0.0001 and p = 0.00014, respectively). The most common clinical manifestations found among β-thal homozygotes were iron overload (90%), splenomegaly (65%) and bone complications (35%), e.g., osteopenia/osteoporosis. We observed that close to 80% of the patients presenting such manifestations had the genotype AA. However, we did not find any significant involvement of the FOXO3 polymorphism in clinical manifestation occurrences. Conclusion: Thus, we concluded that the SNP rs3800231 did not play a significant role as a modifier of the clinical manifestations observed in the β-thal homozygotes studied.
Keywords: Clinical manifestations; Forkhead box O; Genetic polymorphism